EFFECT OF DEVIATION IN POWER QUALITY INDICATORS ON TECHNOLOGICAL COMPONENT LOSSES IN LIVESTOCK - Sinyavsky, A.; Savchenko, V. (Енергетика і автоматика, 2016)
The analysis of the impact of voltage and frequency deviation of the technological component of the current loss of livestock. The method of determining the technological component damage when power quality parameters deviation from the nominal value.